Imperfect transmission of tacit knowledge and other barriers to entrepreneurship - Vesa Kanniainen; Panu Poutvaara (Institute for the Study of Labor (IZA), 2007)
This paper identifies several distortions which create barriers to entrepreneurship. First, in addition to the innate entry cost, there are entry costs caused by regulation. Second, union wage policies raise the opportunity cost of entrepreneurship. Third, inefficiencies in the transmission of tacit knowledge between generations of entrepreneurs can arise: with access to within-family ownership transfer, the outside market for entrepreneurship operates as a lemon's market. This problem becomes relevant when the economic life of a business idea exceeds the active life of an entrepreneur.
Keywords: 330; Unternehmer; Markteintritt; Lohn; Opportunitätskosten; Implizites Wissen; Unternehmensgründung; Berufswahl; Theorie